EVALUATING TROPONIN I FOR MONITORING CARDIAC HEALTH IN CHILDREN WITH BETA-THALASSEMIA MAJOR: INSIGHTS FROM PAKISTAN (The Research of Medical Science Review, 2025)
Cardiac injuries continue to be a primary source of morbidity and mortality in children with MBT, mainly due to iron overload. Cardiac biomarkers, such as Troponin I (Trop I) have appeared as encouraging procedures to identify heart issues at initial stages. This study aimed at addressing key demographic and clinical factors including the role of age, gender and iron chelation therapy in determining cardiac health outcomes in children with MBT, providing insights to conduct focused intervention and enhance patient care.This was a cross-sectional study included 205 children identified with MBT aged between 1-5 years. Patients were categorized into distinct groups that is positive or negative based on their Troponin I levels. Data related to age, gender, residence status (urban/rural), and iron chelation therapy was gathered and analysed by employing chi-square tests. Statistical significance was set at P < .05.Out of the total 205 patients,positive Trop I levels were observed in 31 (15.1%) of the patients. Patients not undergoing chelation therapy had significantly higher levels of elevated Troponin I compared to those receiving chelation therapy (p < 0.001). 27.2% of the rural participants had raised Troponin I levels while only 5.3% of urban participants had positive levels (p = 0.002). Children older then 10 years exhibited an elevated frequency of Troponin I levels (p = 0.034).The findings of this study underscore the preventive role of iron chelation therapy in mitigating cardiac complications and underline the elevated cardiac risk in rural residents along with elder children with MBT. This is consistent with evidence pointing that oxidative stress and myocardial injuries grow with age due to iron deposition in MBT patients, specifically in the absence of chelation therapy.Increased age, residing in rural settings and inadequate chelation therapy were correlated with a elevated frequency Troponin I levels in children having MBT. Routine surveillance of Trop I levels in patients with risk factors of cardiac complexities may lead to timely detection and handling of cardiac involvement, eventually enhancing outcomes for MBT patients.